Chaotic Analysis and Wave Photon Dynamics of Fractional Whitham–Broer–Kaup Model with β Derivative - Muhammad Idrees Afridi; Theodoros E. Karakasidis; Abdullah Alhushaybari (Fractal and Fractional)
This study uses a conformable derivative of order <semantics>β</semantics> to investigate a fractional Whitham–Broer–Kaup (<semantics>FWBK</semantics>) model. This model has significant uses in several scientific domains, such as plasma physics and nonlinear optics. The enhanced modified Sardar sub-equation <semantics>EMSSE</semantics> approach is applied to achieve precise analytical solutions, demonstrating its effectiveness in resolving complex wave photons. Bright, solitary, trigonometric, dark, and plane waves are among the various wave dynamics that may be effectively and precisely determined using the <semantics>FWBK</semantics> model. Furthermore, the study explores the chaotic behaviour of both perturbed and unperturbed systems, revealing illumination on their dynamic characteristics. By demonstrating its validity in examining wave propagation in nonlinear fractional systems, the effectiveness and reliability of the suggested method in fractional modelling are confirmed through thorough investigation.